17O solid-state NMR spectroscopy of A2B2O7 oxides: quantitative isotopic enrichment and spectral acquisition?. Issue 13 (14th February 2018) - Fernandes, Arantxa; Moran, Robert F.; Sneddon, Scott; Dawson, Daniel M.; McKay, David; Bignami, Giulia P. M.; Blanc, Frédéric; Whittle, Karl R.; Ashbrook, Sharon E.
Abstract : Investigation of the conditions required for quantitative isotopic enrichment and the acquisition of quantitative 17 O NMR spectra of ceramic oxides. Abstract : The potential of 17 O NMR spectroscopy for the investigation of A2 B2 O7 ceramic oxides important in the encapsulation of radioactive waste is demonstrated, with post-synthetic enrichment by exchange with 17 O2 gas. For Y2 Sn2 O7, Y2 Ti2 O7 and La2 Sn2 O7 pyrochlores, enrichment of the two distinct O species is clearly non quantitative at lower temperatures (∼700 °C and below) and at shorter times, despite these being used in prior work, with preferential enrichment of OA2 B2 favoured over that of OA4 . At higher temperatures, the 17 O NMR spectra suggest that quantitative enrichment has been achieved, but the integrated signal intensities do not reflect the crystallographic 1 : 6 (O1 : O2) ratio until corrected for differences in T 1 relaxation rates and, more importantly, the contribution of the satellite transitions. 17 O NMR spectra of Y2 Zr2 O7 and Y2 Hf2 O7 defect fluorites showed little difference with any variation in enrichment temperature or time, although an increase in the absolute level of enrichment (up to ∼7.5%) was observed at higher temperature. DFT calculations show that the six distinct resonances observed cannot be assigned unambiguously, as each has contributions from more than one of the five possible next nearest neighbour environments. For La2 Ti2 O7, which adopts a layered perovskite-like structure, little difference in the spectral intensities is observed with enrichment time or temperature, although the highest absolute levels of enrichment (∼13%) were obtained at higher temperature. This work demonstrates that 17 O NMR has the potential to be a powerful probe of local structure and disorder in oxides, but that considerable care must be taken both in choosing the conditions for 17 O enrichment and the experimental acquisition parameters if the necessary quantitative measurements are to be obtained for more complex systems.